ISLAM AS ADAT OR ADAT AS ISLAM? REEXAMINING MINANGKABAU IDENTITY IN CONTEMPORARY GLOBAL CONTEXT - Tuhri, Mufdil (UIN Raden Mas Said Surakarta, 2020)
This article aims to know why â€œadat bersendi Syara, Syara bersendi kitabullahâ€ is so important today for Minangkabau community? In this sense, why is Islam so important to the Minangkabau community? Is it true that the need to reemerging Islam in Minangkabau as it was in the early days, was running similarly or was deviating from its direction and purpose? I will put this on the grassroots view as reflected from the various academic resources of the Minangkabau history of the pre-Colonial and Colonial Islam which became the basis